2008
DOI: 10.1111/j.1574-695x.2008.00444.x
|View full text |Cite
|
Sign up to set email alerts
|

Differentiated S100A7 expression in infected tonsils and tonsils from allergic individuals

Abstract: Palatine tonsils are continuously exposed to microorganisms and antigens and secrete antimicrobial peptides as a first line of defense. S100A7 is a protein with antimicrobial and chemotactic properties. Our aim was to investigate how the expression of S100A7 in human palatine tonsils is affected by inflammatory processes. Tonsils obtained from 109 patients undergoing tonsillectomy were divided into groups of infected and noninfected as well as allergic and nonallergic, based on the results from tonsillar core … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…It should also be mentioned that in contrast to the low levels of S100A7 seen during inflammatory conditions in the upper airways, there are studies demonstrating an enhanced expression and secretion of S100A7 in the skin of patients with AD [25-27]. Moreover, we have previously detected S100A7 in tonsillar epithelium and lymphocytes (CD19 + , CD4 + and CD8 + cells) and found reduced levels in tonsils in response to infection and atopic predisposition [12]. In contrast, blood-derived B and T cells express very low or no levels of S100A7.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…It should also be mentioned that in contrast to the low levels of S100A7 seen during inflammatory conditions in the upper airways, there are studies demonstrating an enhanced expression and secretion of S100A7 in the skin of patients with AD [25-27]. Moreover, we have previously detected S100A7 in tonsillar epithelium and lymphocytes (CD19 + , CD4 + and CD8 + cells) and found reduced levels in tonsils in response to infection and atopic predisposition [12]. In contrast, blood-derived B and T cells express very low or no levels of S100A7.…”
Section: Discussionmentioning
confidence: 96%
“…The PCR primers (β-actin fwd: 5'-GCCAACCGCGAGAAGATG-3', rev: 5'ACGGCCAGAGGCGTACAG-3'; S100A7 fwd: CGTGACGCTTCCCAGCTC-3', rev: 5'-TCATCACGTCTGGTGTATTTGTGA-3') were designed using Primer Express ® 2.0 Software (Applied Biosystems, Foster City, CA, USA) and synthesized by DNA Technology [12]. The thermal cycler was set to perform 95°C for 15 min, followed by 46 cycles of 94°C for 30 s and 55°C for 60 s (initially 65°C, followed by a 2°C decrease for the six first cycles).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tonsil biopsies served as positive controls. 55,56 Negative controls were processed identically omitting primary antibodies, and hematoxylin staining was performed in parallel to visualize tissue architecture and cell distribution. SUPPLEMENTARY MATERIAL is linked to the online version of the paper at http://www.nature.com/mi…”
Section: Patients and Biopsiesmentioning
confidence: 99%
“…Recently, Bryborn et al could show that S100A7/psoriasin is one of several proteins found to be down-regulated in nasal lavage fluid of allergic patients [31] or in infected tonsils as well as in tonsils from allergic individuals [32]. This connection with allergy has been further substantiated with the association of a S100A7/psoriasin gene polymorphism with allergic rhinitis [33].…”
Section: Discussionmentioning
confidence: 99%